Thinking Process of Mathematics Education Students in Problem Solving Proof - Yohanie, Dian Devita; Botchway, Gloria A.; Nkhwalume, Alakanani Alex; Arrazaki, Mohammed (Interval: Indonesian Journal of Mathematical Education, 2023)
This type of research is quantitative research. This study used document analysis, interviews and evidence problem solving task instruments. Qualitative data analysis was carried out interactively. The results of this study are the thinking processes of 2nd semester Mathematics Education students who have high learning achievements. Solving the problem of proof in a direct way, contraposition, and contradiction in the entry phase of the thought process activity obtained is the same, that is, the subject understands the problem by writing down the antecedents as what is known and the consequent as what must be proven. The thinking process of 2nd semester Mathematics Education students who have moderate learning achievements. Solving the problem of proof in a direct way, contraposition, and contradiction in the entry phase of the thought process activity obtained is the same, that is, the subject understands the problem by writing down the antecedents as what is known and the consequence as what must be proven. The thinking process of 2nd semester Mathematics Education students who have low learning achievements. Solving the problem of proof in a direct way, contraposition, and contradiction in the entering phase of the thinking process activity obtained is the same, that is, the subject understands the problem by writing down the antecedents as what is known and the consequent as what must be proven